Development and Formulation of Chocolate-coated Seeds Bar - Anju Praveena Manivarnan; N. Dulcy Thangam (International Journal of Nutritions, 2024)
Vitamins E, D, and B6 minerals like zinc and selenium and amino acids like glutamine all play a role in the body's immune system development. Edible seeds are a great source of protein, healthy fats, fiber, and important minerals like magnesium, potassium, calcium, iron, and zinc in addition to vitamins B1, B2, B3, and E. Examples of edible seeds include pumpkin, flax, sesame, sunflower, mustard, amaranth, oat, barley, black rice, brown rice, quinoa, nigella, and millet seeds. All cells need enough nourishment to grow their immune systems. Based on the sensory assessment 25 percent pumpkin seeds, 10 percent watermelon seeds, 10 percent sunflower seeds, 10 percent flax seeds, 5 percent sesame seeds, 20 percent dates, and 25 percent dark chocolate make up the Chocolate Coated Seeds Bar. Furthermore, including a diverse selection of seeds in your diet can offer a spectrum of nutrients vital for supporting immune function. These seeds contain ample amounts of protein, healthy fats, and fiber, in addition to supplying vital minerals such as magnesium, potassium, calcium, iron, and zinc. They also are ample in nutrients B1, B2, B3, and E, all of which make contributions to average immune gadget characteristic. Examples of seeds include pumpkin, flax, sesame, sunflower, mustard, amaranth, oat, barley, black rice, brown rice, quinoa, nigella, and millet. By ingesting a various array of seeds, people can ensure their cells receive the nourishment needed for ideal immune system improvement and characteristic.
Keywords: Dark chocolate; Dates; Pumpkin seeds; Sesame seeds; Sunflower seeds; Watermelon seeds